2014
DOI: 10.1007/s00167-014-3113-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two different preparations of platelet-rich plasma on synoviocytes

Abstract: PurposeTo analyse the modifications induced by two different platelet-rich plasma (PRP) preparations on osteoarthritis (OA) synoviocytes, by documenting changes in gene expression of factors involved in joint physiopathology.MethodsOA synoviocytes were cultured for 7 days in medium with different concentrations of either P-PRP (a pure platelet concentrate without leucocytes but with a limited number of platelets), L-PRP (a higher platelet concentrate containing leucocytes) or platelet-poor plasma (PPP). Gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 62 publications
9
94
2
Order By: Relevance
“…As mentioned, there are controversial opinions regarding which is the ideal concentration of PLT and WBC in PRP to be used for therapeutic aims in patients with OA [20]. This in vitro research was conducted to complement previous studies [22,[24][25][26] of in vitro cartilage response to several concentrations (25% and 50%) of PRG supernatants from two different PRP preparations (P-PRP and L-PRP).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As mentioned, there are controversial opinions regarding which is the ideal concentration of PLT and WBC in PRP to be used for therapeutic aims in patients with OA [20]. This in vitro research was conducted to complement previous studies [22,[24][25][26] of in vitro cartilage response to several concentrations (25% and 50%) of PRG supernatants from two different PRP preparations (P-PRP and L-PRP).…”
Section: Discussionmentioning
confidence: 94%
“…These complex mechanisms are constantly reported in several studies evaluating the in vitro effects of several PRP preparations and related substances in in vitro systems of joint cell (tissue) inflammation [24,26,34,36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mariani et al (2015) tested the effect of PRP against Escheri chia coli, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa and Enterococcus faecalis, as species potentially involved in bone, soft tissue and wound infections (Zalavras et al, 2004). In the current study, we have selected four microorga nisms that are commonly found in oral and periodontal infections and investigated whether PRP could have in vitro antimicrobial effects against them.…”
Section: Introductionmentioning
confidence: 99%
“…The exclusion of leukocytes has been proven more effective when applied in the treatment of bone defect [29], osteoarthritis [35], and acute tendon injury [36]. In this study, similar platelet concentrations of P-PRP and L-PRP resulted in significantly different ECM production in each individual group.…”
Section: Discussionmentioning
confidence: 68%